Analiza zmian w ukladzie krazenia sportowców wyczynowych z uwzglednieniem póZnych potencjaLów komorowych - Fojt, T.; Mandecki, T.; Fojt, E.; Strzalkowska, D.; Piekarski, M. (Medycyna sportowa, 2000)
Late ventricular potentials (LVP) are regarded as a risk factor for heart rate disturbances of ventricular origin, which may lead to a sudden heart death. Data on their incidence in competitive athletes are scarce and, therefore, the aim of this study was to assess that incidence, taking into account the circulatory changes. A total number of 100 athletes (77 male and 23 female), aged 12-43 years (19 years on the average) and engaged in various sports, participated in the study. Their training experience was at least 5 years (6,5 years on the average). All athletes were subjected to interviews, physical examinations, laboratory assays of blood and urine, spirometry, ultrasonography of the abdominal cavity, and non-invasive cardiovascular examinations (resting and post-exercise ECG, simple and two-dimensional echocardiography with Doppler technique, 24 h Holter ECG recording with subsequent analysis of the sinusoid rhythm and of LVP). Whenever indicated, consultations with specialists were also conducted. Late ventricular potentials were detected in 10 male and 2 female athletes. In two subjects from this group, mitral cup prolapse was detected by echocardiography. In one subject, ventricular arrhythmia of grade IVb (according to Lown) was found by 24 h ECG. No abnormalities were found in the remaining subjects with LVP. The following conclusions were drawn: The incidence of late ventricular potentials in competitive athletes is not a sporadic phenomenon; The presence of late ventricular potentials in competitive athletes is not necessarily associated with the risk of ventricular rhythm disturbances; A more detailed insight into the pathomechanism and causes of the appearance of late ventricular potentials in competitive athletes require further studies.